Friction and wear characteristics of Calophyllum inophyllum biodiesel - Habibullah, M.; Masjuki, Haji Hassan; Kalam, Md. Abul; Zulkifli, N.W.M.; Masum, B.M.; Arslan, A.; Gulzar, M. (Elsevier, 2015)
The purpose of this research is to study the tribological characteristics of Calophyllum inophyllum (Cl) biodiesel as lubricity enhancer by using four ball tribometer. CI biodiesel was produced by using transesterification process and the investigated fuels were pure biodiesel (CIB100), 10% (CIB10), 20% (CIB20), 30% (CIB30) and 50% (CIB50) of biodiesel blended with diesel and pure diesel. Experiment was conducted during 300 s with constant temperature at 27 degrees C and constant sliding speed of 1800 rpm at different load of 40 kg, 50 kg, 63 kg and 80 kg for all tested fuels. The elemental analysis for tested fuel was done using multi element oil analyzer (MOA) and worn surfaces of the ball were examined by SEM/EDX analysis. The average result reveals that diesel fuel shows 16% higher friction coefficient (FC) and 40% higher wear scar diameter (WSD) than pure biodiesel (CIB100). From the elemental analysis, it is found that more metal element (25.3 ppm) is added for CIB100 and highest amount of metal elements were decreased for diesel fuel. The formation of oxide and addition of metal elements are extremely low for CIB20 fuel. Surface morphology showed that CIB20 shows the smaller worn surfaces compared to other diesel-biodiesel blend except CIB100. A further increase in the concentration of biodiesel (CIB30, CIB50), the extrusion of metal is quite higher than CIB20; and thus, CIB20 showed auspicious lubricating performance and highest possibility to form lubricating film without breaking down. (C) 2015 Elsevier B.V. All rights reserved.